2016
DOI: 10.1111/add.13249
|View full text |Cite
|
Sign up to set email alerts
|

Malmö Treatment Referral and Intervention Study (MATRIS)—effective referral from syringe exchange to treatment for heroin dependence: a pilot randomized controlled trial

Abstract: A randomized controlled trial in a syringe exchange programme showed no evidence that a strength-based case management intervention improved attendance for treatment over referral alone. Attendance rates were high in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…We did, however, not have any reason to suspect that the sample was not representative for patients at the OMT clinics. Age and gender distribution were similar to previous Swedish studies on patients in OMT [59, 60]. Use of street drugs and benzodiazepines was comparable to other clinical studies on patients in OMT in the southern Swedish region [9].…”
Section: Discussionsupporting
confidence: 86%
“…We did, however, not have any reason to suspect that the sample was not representative for patients at the OMT clinics. Age and gender distribution were similar to previous Swedish studies on patients in OMT [59, 60]. Use of street drugs and benzodiazepines was comparable to other clinical studies on patients in OMT in the southern Swedish region [9].…”
Section: Discussionsupporting
confidence: 86%
“…In a previous publication, our group showed that SEPs can be efficient for structured referral of opioid-dependent individuals to evidence-based treatment ( 29 ). In this 12-month follow-up of the patients who entered treatment, we demonstrate high-retention rates despite having a study population with a high degree of substance-related problems at baseline, and despite using a rapid referral procedure from an out-of-treatment SEP setting.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of medication was based on clinical characteristics and outside of the study protocol. The methods for this part of the study are described in detail elsewhere ( 29 ). Out of the 75 recruited and randomized patients, 71 started treatment with methadone or buprenorphine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, OST is only available in Sweden through specialist care provision. Buprenorphine-naloxone is the recommended rst-line choice of OST medication [35].…”
Section: Study Design and Settingmentioning
confidence: 99%